Intrapartum ultrasound measurement of the lower uterine segment thickness in parturients with previous scar in labor: a cross-sectional study - Shahla K. Alalaf; Tarek Mohamed M. Mansour; Sileem Ahmad Sileem; Nazar P. Shabila (BMC, 2022)
Abstract Background There is a lack of reliable methods to estimate the risk of uterine rupture or dehiscence during a trial of labor in women with previous cesarean sections. This study aimed to assess the lower uterine segment and myometrial thickness by ultrasonography in women with previous cesarean sections during labor and assess their association with the uterine defect. Methods A cross-sectional study was conducted on 161 women in the active phase of labor having one previous cesarean section. The study was conducted et al.-Azhar University Hospital, Assiut City, Egypt, from March 2018 to March 2019. Ultrasound measurements of lower uterine segment thickness and myometrial thickness were conducted by vaginal and abdominal ultrasound by two observers. The correlation of both thicknesses with the uterine defect was analyzed. Results Uterine defects were reported in 42 women (25.9%), uterine rupture in four women (2.5%), and dehiscence in 38 women (23.5%). The uterine defects were not associated with maternal factors (maternal age, gestational age at labor, body mass index, birth weight, interpregnancy, and inter-delivery interval). Receiver operating curve analysis demonstrated that lower uterine segment thickness was linked with uterine defect, with an area under the curve of 60% (95% CI, 51-70%, P = 0.044). Myometrial thickness was also linked to the uterine defect, with an area under the curve of 61% (95% CI, 52-71%, P = 0.025). Full lower uterine segment thickness of 2.3 mm and myometrial thickness of 1.9 mm were the cutoff value with the best combination of sensitivity and specificity for the uterine defect. Lower uterine segment thickness (OR = 0.49, 95%CI 0.24-0.96) and myometrial thickness (OR = 0.44, 95%CI 0.20-0.94) were significantly associated with the uterine defect. Lower uterine segment thickness (OR = 0.41, 95%CI 0.22-0.76) and myometrial thickness (OR = 0.33, 95%CI 0.16-0.66) were also significantly associated with cesarean section delivery. Conclusion A lower uterine segment thickness of 2.3 mm and myometrial thickness of 1.9 mm during the first stage of labor are associated with a high risk of uterine defects during a labor trial. These measurements during labor can have a practical application in deciding the mode of delivery in women with previous cesarean sections and might reduce uterine rupture.